KEEFEKTIFAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN SOFTWARE ARTICULATE STRORYLINE PADA MATA PELAJARAN BAHASA INDONESIA - Sriyanti Situti Noor; Pattaufi Pattaufi; Abdul Haling; Nurhikmah H Nurhikmah H (Universitas Negeri Makassar, 2023)
This study aims to develop and validate products in the form of interactive learning media using the Indonesian language subject articulate storyline software. The method used in this research is Research and Development (R&D) with the stages of developing the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), the research is carried out up to the evaluation stage. the average value of material experts is 3.5 which is categorized as